Karakteristik Mikoriza Pada Berbagai Lokasi Pertanaman Kakao Sulawesi Tengah - Toana, Moh Rizqi C; Basir, Muhammad; Barus, Henry N (Universitas Tadulako, 2018)
The existence and diversity of mycorrhiza in nature can not be separated from the factors that influence it, such as temperature, light intensity, soil pH and soil nutrient content. The diversity of soil types that have different nutrient content is one of the factors that can influence the existence of mycorrhiza. The purpose of this research is to explain the relationship of mycorrhizal status and soil type characteristic to cocoa plantation area in Central Sulawesi. The location of soil sampling was done in 3 villages ie in the village of Rahmat, Palolo sub-district, Lemban Tongoa village sub district of Palolo, and Saloya village, Sindue sub-district. Analysis of soil physical-chemical properties was carried out in Soil Science Laboratory and mycorrhiza spore observation was conducted in Agronomy Laboratory of Agricultural Faculty of Tadulako University Palu. The research start in October 2016 up to february 2017. The result shows that the average of spores amount in Rahmat Village, Saloya Village and Lemban Tongoa Village is 88, 204 and 224. Root infection is 41.3%, 58.6% and 72.2%. The relationship of soil properties and mycorrhizal depend on the physical and chemical conditions of the soil which causes differences on mycorrhizal spores amount and root infections. Low nutrient of soil was founded high of spores amount and root infections.